Football - Hornby, Hugh; Crawford, Andy (London Dorling Kindersley limited, 2023)
With billions of people watching the 2014 FIFA World Cup and around 265 million players worldwide, football really is the world's best-loved sport. Get in the know and learn about all things football with Eyewitness Football, packed with fascinating facts and amazing images helping football come alive for fanatics everywhere
Arts (sports)
Keywords: Juvenile works; Soccer; Soccer Tournaments